Kepuasan Pasien Terhadap Telemedicine Pada Pelayanan Klinik HIV Di Puskesmas Kecamatan Jatinegara - Fathul Baari; Puteri Fannya; Lily Widjaya; Daniel Happy Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Health services are one of the factors that influence the community's health, and the community's recovery, treatment, and nursing are primarily determined by the health institution. With a system that prioritizes user satisfaction and focuses on five variables content, accuracy, format, convenience of use, and timeliness the goal of this study is to ascertain the degree of satisfaction of Telemedicine users utilizing the EUCS model approach to end-user satisfaction. 56 respondents were given a questionnaire to complete in order to gather data for this study. The study's findings show how pleased telemedicine users are with the following variables: 62.1% are satisfied with the content variable, 57.9% are satisfied with the accuracy variable, 61.1% are satisfied with the format variable, 70.5% are satisfied with the ease of use measure, and 64.2% are dissatisfied with the timeliness variable. The Jatinegara District Health Center, particularly with regard to Telemedicine, can benefit from the study's results, which are linked to five current variables that still require improvement. The degree of user satisfaction will influence how well the system is implemented.